Similar improvements in inhibitory control following low-volume high-intensity interval exercise and moderate-intensity continuous exercise. (November 2020) - Sugimoto, Takeshi; Suga, Tadashi; Tsukamoto, Hayato; Calverley, Thomas A.; Tanaka, Daichi; Takenaka, Saki; Tomoo, Keigo; Dora, Kento; Bailey, Damian M.; Isaka, Tadao; Hashimoto, Takeshi
Abstract: Objectives: We previously demonstrated that a traditional high-volume (HV) high-intensity interval exercise (HIIE) was more effective in improving post-exercise inhibitory control (IC) than moderate-intensity continuous exercise (MCE). Nevertheless, because HV-HIIE is performed with a higher volume and longer duration, it may result in decreased adherence to this exercise for some individuals. In this study, we compared the effect of a practical low-volume (LV) HIIE to that of MCE on post-exercise IC improvements. Design: Twenty healthy males performed both LV-HIIE and MCE on a cycle ergometer in a crossover design. Method: LV-HIIE was consisted of ten 1-min bouts at 90% of the peak oxygen consumption (VO2 peak ) with 1-min active recovery at 30% of VO2 peak, which had a total duration of 20 min. MCE was performed for 40 min at 60% of VO2 peak . To evaluate IC, the Stroop test was administered before exercise, immediately after exercise, and every 10 min during the 30-min post-exercise recovery period. Results: IC significantly improved immediately after LV-HIIE and MCE compared with that before each exercise (both P s < 0.05). The improved IC remained significant until the 20-min post-exercise recovery period for both protocols (all P s < 0.05). The degrees of post-exercise IC improvements throughout the 30-min post-exercise recovery period did not differ significantly between protocols. Conclusions: These findings demonstrated that despite lower exercise volume and shorter exercise duration, LV-HIIE could improve post-exercise IC similar to MCE. Highlights: High-intensity interval exercise (HIIE) significantly improves post-exercise inhibitory control (IC). This study compared the effect of low-volume (LV) HIIE and moderate-intensity continuous exercise (MCE) on post-exercise IC. Despite lower exercise volume and shorter exercise duration, LV-HIIE could improve post-exercise IC similar to MCE.